Value of fine-needle aspiration cytology in diagnosis of Hodgkin’s lymphoma and anaplastic large cell lymphoma : one centre experience - Ostojić Kolonić, Slobodanka (Array, 2010)
Cilj studije bio je procijeniti vrijednost i ograničenja citologije u dijagnostici i razlikovanju Hodgkinovog limfoma (HL) i anaplastičnog velikostaničnog limfoma (ALCL)